2013
DOI: 10.1016/j.nuclphysb.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Integrable Scalar Cosmologies I. Foundations and links with String Theory

Abstract: We build a number of integrable one-scalar spatially flat cosmologies, which play a natural role in inflationary scenarios, examine their behavior in several cases and draw from them some general lessons on this type of systems, whose potentials involve combinations of exponential functions, and on similar non-integrable ones. These include the impossibility for the scalar to emerge from the initial singularity descending along asymptotically exponential potentials with logarithmic slopes exceeding a critical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
175
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 75 publications
(178 citation statements)
references
References 105 publications
3
175
0
Order By: Relevance
“…The most popular integrable cosmological model is the model with a minimally coupled scalar field and a self-interaction exponential potential [33,34]. In [35], the general classification of integrable cosmological models based on scalar fields was suggested and studied in great detail. Integrable models with nonminimally coupled scalar fields have been found in [22].…”
Section: Introductionmentioning
confidence: 99%
“…The most popular integrable cosmological model is the model with a minimally coupled scalar field and a self-interaction exponential potential [33,34]. In [35], the general classification of integrable cosmological models based on scalar fields was suggested and studied in great detail. Integrable models with nonminimally coupled scalar fields have been found in [22].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the transition at γ = 1 and the analogy with a Newtonian particle in a viscous medium were reviewed in [26,27], and more recently in [28]. Here I shall only mention, in passing, some intriguing facts, drawn largely from [17]:…”
Section: Climbing Scalars In Briefmentioning
confidence: 99%
“…• if Φ s is somehow stabilized, a space-time filling p-brane that couples to the dilaton, in the string frame, proportionally to e − α φ , contributes in four dimensions an exponential potential [26,27] V ∼ e 2 γ ϕ ,…”
Section: Climbing Scalars In Briefmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate investigation was also devoted to determine a list of one field integrable potentials [28] and to discuss their possible inclusion into N = 1 supergravity by means of suitable superpotentials [29]. It was shown that such type of inclusion is quite difficult and can be realized only in very few cases [29].…”
Section: Introductionmentioning
confidence: 99%